Consensus, dissension and precision in group decision making by means of an algebraic extension of hesitant fuzzy linguistic term sets - Montserrat-Adell, Jordi; Agell, Núria; Sánchez, Mónica; Javier Ruiz, Francisco (Information fusion, 2018)
•A collective degree of consensus for group decision making with HFLTSs is defined.•An individual degree of consensus for group decision making with HFLTSs is defined.•These degrees explicitly take into account how far non-overlapping assessments are.•A comparison study with existing measures is presented.•A precision-dissension profile for each decision maker is presented. [Display omitted] Present measures of the degree of agreement in group decision-making using hesitant fuzzy linguistic term sets allow consensus or agreement measurement when decision makers’ assessments involve hesitance. Yet they do not discriminate with different degrees of consensus among situations with discordant or polarized assessments. The visualization of differences among groups for which there is no agreement but different possible levels of disagreement is an important issue in collective decision-making situations. In this paper, we propose new collective and individual consensus measures that explicitly consider the hesitance of the decision makers’ hesitance in giving an opinion and also the gap between non-overlapping assessments, thus allowing the measurement of the polarization present within the group’s opinions. In addition, an expert’s profile is defined by considering the expert’s behavior in previous assessments in group decision-making processes in terms of precision and dissension.